Relation of neutrophil/lymphocyte ratio to resistant hypertension - Dagli, Necati; Dogdu, Orhan; Senarslan, Omer; Yucel, Hasan; Kaya, Hakki; Akpek, Mahmut; Eriten, Semih (The European Research Journal, 2016)
Objectives. Resistant hypertension has unfavourable effects on cardiovascular and other systems. The aim of this study was to investigate the association of neutrophil/lymphocyte (N/L) ratio and resistant hypertension.Methods. A total of 140 patients were included in the study. Ambulatory 24-hour blood pressure monitoring, transthoracic echocardiography and blood sample analyzing were performed in all patients. There were 60 patients with resistant hypertension group (mean age=55.1±9.7 years) and 80 patients with non-resistant hypertension group (mean age=56.8±14.1 years).Results. Mean neutrophil levels were significantly higher in resistant hypertension group (71.7±6.1% vs. 65.9±5.4%, p